Cooperative moves in a non-cooperative game. (24th August 2007) - Jones, Robert T.; Veendorp, E.C.H.
We try to show that the use of alternating decision making in an infinitely repeated prisoners' dilemma type game may enable sophisticated players to achieve perpetual cooperation starting from any initial position and without any prior communication, and that the ability of players to do so depends on the relative magnitudes of the pay-offs in the stage game.